Gratitude - Hugues, Juan (1972)
Bishop Ricardo Durand Flores, sj. Archbishop of Cuzco, after many consultations and studies, began in 1968, with six Bishops and Prelates from the southern Andean region of Peru, the Andean Pastoral Institute.